KREATIVITAS DAN INOVASI REDAKSI @NTVNEWS.ID: KOMODIFIKASI BERITA MENJADI VIDEO PENDEK DI INSTAGRAM - Depvia Faizah Tsaniyah; Iin Soraya; Yogi Ariska (CV Edujavare Publishing, 2025)
This study aims to reveal how the creativity and innovation of the @ntvnews.id editorial team play a role in the process of commodifying news into short videos that are adjusted to the characteristics of Instagram social media. Using a descriptive qualitative method, data was obtained through interviews, observations, and documentation. The results of the study show that the editorial team modifies news into interesting visual content that is in accordance with the characteristics of the social media audience. Innovation is seen from the video format, narrative style, and the use of platform algorithms. The division of specialized tasks supports production efficiency. These findings confirm that creativity and innovation are important strategies in maintaining the existence of digital media.